Multimodal Bone Metastasis-associated Epidermal Growth Factor Receptor Imaging in an Orthotopic Rat Model. - Bäuerle, Tobias; Gupta, Suresh; Zheng, Shaokuan; Seyler, Lisa; Leporati, Anita; Marosfoi, Miklos; Maschauer, Simone; Prante, Olaf; Caravan, Peter; Bogdanov, Alexei (Radiology: Imaging Cancer, 2021)
Purpose To develop multimodality imaging techniques for measuring epidermal growth factor receptor (EGFR) as a therapy-relevant and metastasis-associated molecular marker in triple-negative mammary adenocarcinoma metastases. Materials and Methods An orthotopic bone metastasis EGFR-positive, triple-negative breast cancer (TNBC) model in rats was used for bioluminescence imaging, SPECT/CT, PET/CT, and MRI with quantitative analysis of transcripts (n = 22 rats). Receptor-specific MRI of EGFR expression in vivo was performed by acquiring spin-echo T1-weighted images after sequential administration of a pair of anti-EGFR antigen binding fragments, F(ab')2, conjugated to either horseradish peroxidase or glucose oxidase, which have complementing activities, as well as paramagnetic (gadolinium[III]-mono-5-hydroxytryptamide of 2,2',2''-(10-(2,6-dioxotetrahydro-2H-pyran-3-yl)-1,4,7,10-tetraazacyclododecane-1,4,7-triyl)triacetic acid, or Gd-5HT-DOTAGA) or positron-emitting (gallium 68-5HT-DOTAGA) substrates for MRI and PET/CT imaging, respectively. EGFR expression was confirmed by quantitative reverse transcriptase polymerase chain reaction and immunohistochemical analyses to compare with image findings. Results After surgical intraarterial delivery of TNBC cells, rats developed tumors that diverged into either rapidly growing osteolytic or slow-growing nonosteolytic tumors. Both tumor types showed receptor-specific initial MRI signal enhancement (contrast-to-noise ratio) that was three to six times higher than that of normal bone marrow (29.4 vs 4.9; P < .01). Micro PET/CT imaging of EGFR expression demonstrated a high level of heterogeneity with regional uptake of the tracer, which corresponded to region-of-interest MRI signal intensity elevation (121.1 vs 93.3; P < .001). Analysis of metastases with corroboration of imaging results showed high levels of EGFR protein and messenger RNA, or mRNA, expression in the invasive tumor. Conclusion Convergence of multimodal molecular receptor imaging enabled comprehensive assessment of EGFR overexpression in an orthotopic model of TNBC metastasis. Keywords: Animal Studies, Molecular Imaging-Cancer, MR-Contrast Agent, Radionuclide Studies, Skeletal-Appendicular, Metastases Supplemental material is available for this article. © RSNA, 2021.
EVALuna2:469075